2022
DOI: 10.3389/fnhum.2022.824730
|View full text |Cite
|
Sign up to set email alerts
|

Load-Induced Changes of Inter-Limb Asymmetries in Dynamic Postural Control in Healthy Subjects

Abstract: Inter-limb asymmetries are associated with a higher potential risk for non-contact injuries. Differences in function or performance between the limbs might lead to imbalances and promote instability, increasing the potential risk for injuries. Consequently, an investigation of inter-limb asymmetries should be included in injury risk assessment. Furthermore, since non-contact injuries mainly occur under loaded conditions, an investigation of load-induced changes of inter-limb asymmetries can provide additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In this same analysis, it was observed that 39% of the evaluated older adults present asymmetries over 15% in the LL. In this sense, there is evidence that relates asymmetries between LL with a higher risk of injury [ 26 ] and risk of falling in older adults [ 29 ]. Likewise, although there is no scientific consensus to determine the percentage of asymmetry that generates a potential risk of suffering injuries or falls, it has been identified that an asymmetry ≥ 15% corresponds to an indicator of risk in healthy subjects [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this same analysis, it was observed that 39% of the evaluated older adults present asymmetries over 15% in the LL. In this sense, there is evidence that relates asymmetries between LL with a higher risk of injury [ 26 ] and risk of falling in older adults [ 29 ]. Likewise, although there is no scientific consensus to determine the percentage of asymmetry that generates a potential risk of suffering injuries or falls, it has been identified that an asymmetry ≥ 15% corresponds to an indicator of risk in healthy subjects [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, observing the dispersion of our results, it is evident that several older adults with levels of asymmetries place a population at risk (16 out of 41 older adults evaluated), especially for falling [ 29 ]. However, the evidence suggests that asymmetry analyses should be performed on a case-by-case basis and consider possible modifying factors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations